Korean wave’s influences on Indonesian beauty standard depicted in skincare advertisements: Critical discourse analysis - Pramusita, Santa Maya (LingTera, 2021)
This research aims to disclose the influence of the Korean wave toward the Indonesian beauty standards reflected in the skincare advertisements. A descriptive qualitative method with the approach of critical discourse analysis is employed to obtain the research objective. The media are Viva moisturizer advertisement appeared in the early 2000s, Wardah White Treatment Essence advertisement published in 2019, and Laneige BB Cushion Korean advertisement as a part of intertextuality. The 19 year-publication gaps is deliberately presented to show how the shift of beauty myth takes place. The data taken were in words, phrases, and sentences, which were then analyzed using Fairclough’s three-dimensional approach. The results showed that Viva attracted consumers’ attention using similes, simple present tense, keywords repetition, and positive adjectives. On the other side, Wardah used hyperbole, possessive pronoun, and scientific terminology to convince the consumers of their product’s superiority, in line with Laneige’s advertisement. Regarding the discursive features, these three advertisements were similar in that they used logos, flattery, puffery, and positive image representation. Lastly, the analysis of social practice indicated that the influence of the Korean wave was clearly seen on Wardah’s commercial, which portrayed beauty as Laneige did. They tried shaping consumers’ beliefs that beauty means having a white, flawless, and glowing face. Thus, the beauty myth had changed from the previous era. This resembles Bourdieu’s notion of field, capital, and Doxa.